2019
DOI: 10.26668/businessreview/2019.v4i1.105
|View full text |Cite
|
Sign up to set email alerts
|

Does environmental cost affect Japanese Firms' performance?

Abstract: This article aims to examine the effect of environmental cost to financial performances, measured by profitability and firm value in Japanese chemical industry during 2012-2015.  Examining about this matter in Japan case is suitable since the government has settled guidelines that assist the companies to record and report their activities in environmental preservation. This study focuses on chemical industry in Japan because the industry has been potential to create hazardous wastes along with its daily busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
0
9
0
4
Order By: Relevance
“…The study [22] looked at the impact of environmental costs on financial performance in the Japanese chemical sector, as assessed by profitability and company value, from 2012 to 2015. Environmental costs have a negative impact on return on asset, net profit margin, and Tobin's Q, but have no impact on return on equity or price earnings ratio, according to the findings.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The study [22] looked at the impact of environmental costs on financial performance in the Japanese chemical sector, as assessed by profitability and company value, from 2012 to 2015. Environmental costs have a negative impact on return on asset, net profit margin, and Tobin's Q, but have no impact on return on equity or price earnings ratio, according to the findings.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…On the other hand, Nuzula (2019) found that profitability did not affect environmental costs. ROA and NPM, as measures representing the relationship between these two variables, indicate that environmental costs would not provide monetary feedback in the short term.…”
Section: Environmental Performancementioning
confidence: 96%
“…Çalışma sonunda, Nijerya'da bulunan ve incelenen petrol ve gaz şirketlerinin çevre harcamaları ile net karı arasında anlamlı bir ilişkiye rastlanmamıştır. Nuzula (2019) yapmış olduğu çalışmasında Japon kimya endüstrisinde çevresel maliyetlerin, kârlılık ve firma değeri ile ölçülen finansal performansa etkisini incelemiştir. Çalışmada kimya endüstrisinde faaliyet gösteren 27 firmanın 2013-2015 dönemindeki verilerinden yararlanılmıştır.…”
Section: Literatür İncelemesiunclassified